Política de formação continuada de professores do ensino fundamental I, no município de Francisco Beltrão - PR entre os anos de 2013 e 2022: aportes teóricos e legais. - Bernardi, Valdicleia Aparecida Castro (2024)
The main objective of this research is to analyze the policy of continuing education for elementary school teachers in the municipality of Francisco Beltrão – PR, between 2013 and 2022, with an emphasis on theoretical and practical aspects. The specific objectives structure the chapters of this dissertation and can be described as: understanding the neoliberal reform of the State and education and its complex agenda disputes, as well as its impacts on teacher training; identifying the conceptual and practical knowledge necessary for continuing education and the construction of teacher identity; and analyzing the continuing education policy for elementary school teachers in the municipality during the analyzed period, observing its limits and perspectives. The research questions are: To what extent does the continuing education offered in Francisco Beltrão enable the construction of a teacher identity? What are the training needs at the elementary school level? Do the training processes consider the inseparability between theory and practice? Is there a historical path of continuity in the training programs, or are they isolated efforts? Does the municipality's training policy only meet market demands, or does it address educational needs in a contextualized manner? We adopted a qualitative approach, as it allows for a richness of descriptive detail through information collected from official documents that regulate and describe teacher training, as well as data analysis on the municipality's policies. The structure of the dissertation consists of three chapters that intertwine in terms of theory and argumentation. The first chapter, titled “State and Education Reform via Neoliberalism: A Complex Agenda Dispute”, focuses on understanding how neoliberal agendas have shaped teacher training practices and local educational structures, considering the different stakeholders involved, the interests at play, and the implications of these changes for the quality of education and the role of teachers in this context. The second chapter, titled “Conceptual Knowledge: Expectations for Continuing Education and Teacher Identity”, discusses the theoretical and conceptual knowledge required by teachers throughout their training, as well as expectations for ongoing teacher education, which involves the continuous pursuit of updates in new theories, pedagogical practices, and educational technologies. These processes contribute to the formation of teacher identity, their values, and practices, as continuing education strengthens this identity, allowing educators to develop a broader and more contextualized understanding of their role in society and in student development. In the final chapter, we delve into the “Theoretical and Legal Aspects of the Continuing Education Policy for Elementary School Teachers in the Municipality of Francisco Beltrão between 2013 and 2022”. In this phase of the research, we examined official documents that establish and describe teacher training programs, in addition to analyzing data related to the training processes in the municipality. Our hypothesis is that these documents will provide a comprehensive view of the policies and practices of continuing education for teachers in Francisco Beltrão over the past decade.